Penerapan Literasi Keuangan Syariah Untuk Anak Panti Asuhan Sebagai Pondasi Ekonomi Masa Depan - Mustamin, Sitti Walida; Nurul Izmi Muhajir; Afifah Adliah; Arini; Anggraeni Ramadhani; M. Ridwan Syafruddin; Sri Ayu Ainun; Muhammad Aldi Naufal Saputra; Aidil Marzuki; Riski Aulia; Arjuna Amrum Amir (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity aims to improve Islamic financial literacy among orphanage children as an effort to equip them with the knowledge and skills needed to manage their finances wisely. In this context, Islamic financial literacy includes an understanding of the basic principles of finance in accordance with Islamic law, including savings management, investment, and avoidance of usury. This program is implemented through a series of socialization of material delivery, interactive training, and financial management simulations designed to make learning interesting and easy to understand. By improving Islamic financial literacy, it is hoped that orphanage children can build a strong economic foundation, which will not only benefit themselves, but also the community around them. Through this activity, we hope to create a generation that is more aware of the importance of good and ethical financial management, and is able to contribute to sustainable economic development in the future.